Mushrooms Dehydration in a Hybrid-Solar Dryer, Using a Phase Change Material - Reyes-Salinas, A; Mahn-Osses, A (Elsevier Ltd, 2014)
Mushrooms were dehydrated in a hybrid solar dryer provided with a solar panel of a total exposed surface of 10 m2, electric resistances and paraffin wax as a phase change material. Mushrooms were cut in 8 mm or 12 mm slices. At the outlet of the drying chamber the air was recycled (70% or 80%) and the air temperature was adjusted to 60 °C. At the outlet of the solar panel the air temperature rose up to 30°C above the ambient temperature, depending on solar radiation level. The effective diffusivity, estimated by the Simplified Constant Diffusivity Model, considering or not shrinkage, fluctuated between 2.5·10-10 m2/s and 8.4·10 -10 m2/s with R2 higher than 0.99, agreeing with values reported in literature. The empirical Page s model resulted in a better adjustment, with R2 above 0.998. In all runs the dehydrated mushrooms showed a notorious darkening and shrinkage. Rehydration assays at 30°C showed that in less than 30 min rehydrated mushrooms reached a moisture content of 1.91 (dry basis). Rehydrated mushrooms had a higher hardness compared with fresh mushrooms. The Simplified Constant Diffusivity Model and the Peleg s model adjusted to the rehydration data with RMSE values below 0.080. Thermal efficiency fluctuated between 22% and 62%, while the efficiency of the accumulator panel varied between 10% and 21%. The accumulator allowed reducing the electric energy input. © 2014 Elsevier Ltd. All rights reserved.